2021
DOI: 10.3390/en14061668
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Evaluation of a Home Energy Management System for Power Saving

Abstract: In the context of the ongoing global warming, with environmental concerns regarding the greenhouse gas emissions due to our increasing energy consumption, smart energy management solutions have gained popularity as they have the potential to reduce our impact on the environment and also on our budgets. This paper proposes one of the most affordable designs for an autonomous, microcontroller-based demand-side energy management system to be installed in a home environment where it reduces the standby power consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Concerns and obstacles related to smart technology, such as implementation and privacy, are also addressed. It provides one of the lowest-priced solutions for an autonomous, microcontroller-based demand-side energy monitoring system for use in a residential setting to decrease the standby power consumption of the devices under supervision [12]. It also monitors and adjusts the lighting to reduce energy use further.…”
Section: Related Workmentioning
confidence: 99%
“…Concerns and obstacles related to smart technology, such as implementation and privacy, are also addressed. It provides one of the lowest-priced solutions for an autonomous, microcontroller-based demand-side energy monitoring system for use in a residential setting to decrease the standby power consumption of the devices under supervision [12]. It also monitors and adjusts the lighting to reduce energy use further.…”
Section: Related Workmentioning
confidence: 99%
“…Architectural Overview Operation Consumption Reduction [6] GSM The central component of the system is an Arduino UNO board, of which 20 pins are used for the interface of sensors and actuators. To detect the presence of the user, three PIC HC-SR501 modules are connected to the Arduino.…”
Section: Ref/com Techmentioning
confidence: 99%
“…The forecasting model took into consideration the uncertainty of future energy consumption and prices. In [ 18 ], the authors presented an optimization approach for scheduling household appliances. The results demonstrated that energy usage and utility bills were lowered as a result of the HEMS strategy.…”
Section: Introductionmentioning
confidence: 99%